Niveles de conciencia fonológica en estudiantes de primer grado de instituciones educativas públicas de Pachacútec - De la Cruz Valentín, Ayda (2010)
The purpose of this study was to determine the performance of phonological awareness at different levels in 250 children from first grade of public educational institutions Pachacútec. Students come mostly from migrant families from across the country and belong to low socioeconomic status. This ability was evaluated using the Test of metalinguistic skills (THM) from Gómez, Valero, Buades and Pérez (1995) adapted in Perú by Panca (2000). The results indicate that only 1.6% of the sample tested has a breakthrough performance in phonological awareness while 98.4% is below the expected scores. An analysis between the subtests (THM) found that metaphonological performance was better in the levels of rhyme and phonemes versus syllables which would explain the difficulties in learning to read.